Comparing the Student Learning Outcomes and Teaching Satisfaction of Conventional Lecture and Team-Based Learning Methods: Student Learning Outcomes and Teaching Satisfaction - Shoukat, Marium; Saqib, Hammad Ahmad; Tahir, Farah Naz; Chema, Sadia Imran; Qureshi, Zahid Habib; Farooq, Bakhtawar (Pakistan Journal of Health Sciences, 2024)
Students hesitate to pursue subjects like biochemistry and manifest a lack of participation and motivation during conventional lectures. However, team-based learning facilitates interactive learning through discussion and improves learning outcomes. Objective: To compare the student learning outcomes and teaching satisfaction from team-based learning and conventional learning among medical students. Methods: A prospective study was conducted in Rahbar Medical College from December 2023 to May 2024. A total of 100 undergraduate students aged from 19 to 22 years studying biochemistry course were selected for the study. A total of 16 classes were conducted for teaching biochemistry among which 8 were taught by conventional lecture method and the rest 8 were taught by team-based learning. Students were instructed to fill out a student satisfaction scale questionnaire consisting of 20 questions at the end of the last TBL session. Results: The mean score of conventional lectures was 11.85 ± 1.54 with a maximum score of 15.5 and minimum score of 10 out of 20. The highest score was obtained by group assessment readiness test i.e. 16.25 ± 1.05. The mean score of conventional and TBL methods was 14.10 ± 1.12, with a minimum score of 12.20, and a maximum score of 15.95 out of 20 (P=0.016). Overall satisfaction scores in females were higher than in males (p<0.001). The mean student satisfaction score was 81.27 ± 9.18. Conclusion: Team-based learning yields better learning outcomes and teaching satisfaction in medical students as compared to conventional lecture methods. These results were also improved in female students than in males.